Copper mediated controlled radical copolymerization of styrene and 2-ethylhexyl acrylate and determination of their reactivity ratios - Koiry, Bishnu P.; Singha, Nikhil K. (Frontiers in Chemistry, 2014)
Copolymerization is an important synthetic tool to prepare polymers with desirable combination of properties which are difficult to achieve from the different homopolymers concerned. This investigation reports the copolymerization of 2-ethylhexyl acrylate (EHA) and styrene using copper bromide (CuBr) as catalyst in combination with N,N,N’,N”,N”- pentamethyldiethylenetriamine (PMDETA) as ligand and 1-phenylethyl bromide (PEBr) as initiator. Linear kinetic plot and linear increase in molecular weights versus conversion indicate that copolymerization reactions were controlled. The copolymer composition was calculated using 1H NMR studies. The reactivity ratio of styrene and EHA (r1 and r2) were determined using the Finemann-Ross (FR), inverted Finemann-Ross (FR) and Kelen-Tudos (KT) methods. Thermal properties of the copolymers were also studied by using TGA and DSC analysis.